Perceptions of EFL Students Regarding the Use of Natural Language Processing AI for Improving English Writing Skill - Munigarim, Dewi; Khatimah, Khusnul (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2024)
In the digital age, rapid technological advancements have introduced various Artificial Intelligence (AI), significantly influencing education, particularly in language learning. This study focuses on ChatGPT, a Natural Language Processing model developed by OpenAI, exploring its transformative potential in language generation tasks, including writing. Ethical considerations in AI development, emphasized by organizations like OpenAI, are crucial for responsible deployment. ChatGPT promises to modernize language learning, particularly in English as a Foreign Language (EFL) context, by aiding learners in writing tasks. Writing skills are essential for language proficiency, encompassing cognitive, emotional, and social dimensions. The integration of AI in language learning not only enhances writing proficiency but also fosters creativity and critical thinking. However, student perceptions of AI tools like ChatGPT vary, with concerns about creativity hindrance and reliance on technology. Employing a mixed-methods approach, this study investigates EFL students' perceptions of ChatGPT's impact on writing skills, revealing predominantly positive responses alongside challenges such as internet connectivity issues and reliance on paid versions. Overall, ChatGPT offers opportunities to enhance writing skills, although ethical deployment and user dependency considerations are paramount.